Role of Natural Autoantibodies and Natural IgM Anti-Leucocyte Autoantibodies in Health and Disease - Lobo, Peter Isaac (Frontiers in Immunology, 2016)
We review how polyreactive natural IgM autoantibodies (IgM-NAA) protect the host from invading micro-organisms and host neo-antigens that are constantly being produced by oxidation mechanisms and cell apoptosis. Secondly, we discuss how IgM-NAA and IgM-ALA inhibits auto-immune inflammation by anti-idiotypic mechanisms, enhancing removal of apoptotic cells, masking neo-antigens and regulating the function of dendritic cells (DC) and effector cells. Thirdly, we review how natural IgM prevents autoimmune disorders arising from pathogenic IgG autoantibodies, triggered by genetic mechanisms (e.g. SLE) or micro-organisms, as well as by auto reactive B and T cells that have escaped tolerance mechanisms. Studies in IgM knockout mice have clearly demonstrated that regulatory B and T cells require IgM to effectively regulate inflammation mediated by innate, adaptive and auto-immune mechanisms. It is therefore not surprising why the host positively selects such autoreactive B1 cells that generate protective IgM-NAA, which are also evolutionarily conserved. Fourthly, we show that IgM-ALA levels and repertoire can vary in normal humans and disease states and this variation may partly explain the observed differences in the inflammatory response after infection, ischemic injury or after a transplant. We also show how protective IgM-NAA can be rendered pathogenic under non-physiological conditions. We also review IgG-NAA that are more abundant than IgM-NAA in plasma. However, we need to understand if the (Fab)2 region of IgG-NAA has physiological relevance in non-disease states, as in plasma, their functional activity is blocked by IgM-NAA having anti-idiotypic activity. Some IgG NAA are produced by B2 cells that have escaped tolerance mechanisms and we show how such pathogenic IgG-NAA are regulated to prevent autoimmune disease. The Fc region of IgG-NAA can influence inflammation and B cell function in-vivo by binding to activating and inhibitory FcR. IgM-NAA has therapeutic potential. Polyclonal IgM infusions can be used to abrogate on-going inflammation. Additionally, inflammation arising after ischemia induced kidney injury e.g. during high-risk elective cardiac surgery or after allograft transplantation, can be abrogated by pre-emptively infusing polyclonal IgM or DC pretreated ex-vivo with IgM or by increasing in-vivo IgM with a vaccine approach. Cell therapy is appealing as less IgM will be required.